Examining the Impact of Generative AI Content on Impulse Buying Behavior in Social Commerce - Huang XiaoFeng; Anton Wachidin Widjaja (International Journal of Applied Business and International Management, 2025)
The growing adoption of generative artificial intelligence (AI) in social commerce, particularly for promotional videos and live-streaming scripts, has transformed consumer persuasion processes, yet its role in stimulating impulse buying remains insufficiently examined. This study investigates the effects of AI-generated content attributes (credibility, attractiveness, novelty, and trust) on impulse buying tendency, with perceived interactivity examined as a mediating variable. Survey data were collected from 266 Indonesian social commerce users and analyzed using multiple regression and mediation analysis via the SPSS PROCESS macro (Model 4) with 5,000 bootstrap samples. The results indicate that credibility (? = 0.341, p 0.001), attractiveness (? = 0.178, p = 0.003), novelty (? = 0.141, p = 0.019), and trust (? = 0.125, p = 0.025) have significant positive effects on impulse buying tendency. Mediation analysis shows that perceived interactivity partially mediates all relationships, with the strongest indirect effect observed for trust (indirect effect = 0.203). The findings extend impulse buying theory to AI-mediated contexts and suggest that social commerce practitioners should prioritize interactive and credible AI content to enhance consumer engagement and unplanned purchasing behavior.